Prevalence of Helicobacter Pylori infection in children with iron deficiency anemia admitted in tertiary care hospital - Mohammed Muzzamil; Choudhary, Mukesh; Nagar, Manoj; Vishnoi SK; Choudhary, Sandeep; Jora, Rakesh; Kothari, Sunil (Asian Journal of Medical Sciences, 2022)
Background: Iron deficiency anemia (IDA) can result from both physiological and pathological events, the etiology of underlying IDA should be determined. Helicobacter pylori infection in children has mostly been associated with recurrent abdominal pain, gastric dyspepsia, or duodenal-ulcer. Other extra-digestive tract conditions such as iron deficiency or IDA have been recently related to the H. pylori infection. Aims and Objectives: To find out the prevalence of H. pylori infection in children aged 2–18 years with IDA in a tertiary care hospital. Materials and Methods: Across-sectional observational study was carried out in the Department of Paediatrics, Dr. S.N. Medical College, Jodhpur for a period of 1 year. A total of 52 children aged between 2 and 18 years with anemia (as per the WHO criteria of anemia) were evaluated for complete blood count, peripheral blood film and serum ferritin, serum iron, total iron-binding capacity (TIBC), Upper gastrointestinal endoscopy and two biopsy specimen evaluated for H. pylori and histopathological changes. Normally distributed data means were compared using student’s t-test unpaired and paired. Proportions were compared using Chi-square or Fisher’s exact test. Results: The prevalence of H. pylori in our study population was 32.69%. In children with H. pylori infection mean S.iron was 25.78±10.24 μg/dl, mean S.TIBC 544.66±91.68 μg/dl, and mean S.ferritin was 6.07±3.00 μg/dl. There was statistically significant difference in serum iron, S.TIBC and S.ferritin between children having H. pylori infection and without H. pylori infection(P<0.001). Conclusion: There is an association of IDA and H. pylori infection. Therefore prevention and eradication of H. pylori infection might be helpful to prevent IDA, especially in those patients who are not responding to usual treatment.